Conserved aromatic residues as determinants in the folding and assembly of immunoglobulin variable domains. (February 2016) - Campion, Stephen R.
Highlights: Immunoglobulin VH and VL domains exhibit both shared and unique sites of conservation. Ig heavy- and light-chains share critical sites of conserved aromaticity. Conserved aromaticity is symmetrically concentrated in the VH–VL interface. A role for aromaticity in both the folding and assembly of antibody structure is postulated. Abstract: Detailed analysis of amino acid distribution, focusing on the "framework" regions of both heavy- and light-chain variable immunoglobulin (Ig) domains, distinguished those conserved sequence elements shared by both heavy-chain (VH) and light-chain (VL) domains from those conserved determinants unique to either VH or VL domains alone. Mapping of conserved chemical functionality onto characterized PDB structures showed the analogous placement and utilization of shared determinants in VH and VL structures that are generally similar. Identical Arginine–Aspartic acid ion-pairs located symmetrically on the lateral surfaces of VH and VL domains, respectively, as well as paired glutamine residues that constitute a central contact site between VH and VL domains represent clearly shared molecular features. Three sites of shared aromaticity were found localized to symmetrical sites lining the inaccessible interface of the VH–VL duplex, suggesting an expanded role for strategically conserved aromatic residues from a postulated determinant of individual Ig domain folding to now implicate conserved aromatic sites in the subsequent multi-subunit assembly of native antibody superstructure. Differential domain-specific conservation, representing evolutionary diversification and molecular asymmetry between heavy- and light-chain variable domains was limited, but included amino acids from each functional class and must be evaluated with regard to their possible involvement in heterologous aspects of IgV protein structure–function.